Menembus Kelas Menengah: Analisis Interaksi Pendidikan dan Pekerjaan terhadap Mobilitas Ekonomi Rumah Tangga di Provinsi Jambi - Adriani, Evi; Alhudori, M. (Universitas Batanghari Jambi, 2025)
This study aims to identify factors influencing household economic mobility towards the middle class, specifically examining the influence of education, employment status, employment sector, and their interactions, while considering other socio-demographic control variables. This study uses a quantitative approach with a household-based cross-sectional data analysis design. This study uses a binary logistic regression model. The data used comes from the March 2024 National Socioeconomic Survey (Susenas). The unit of analysis is the household, with the unit of observation being the head of the household. The results show that education, employment status, and the interaction between the two are the most significant main explanatory variables in driving household economic mobility towards the middle class in Jambi Province. The influence of control variables (age of the head of the household, place of residence, migration status) is also significant on the chances of households entering the middle class.